Pancreatic carcinosarcoma mimics malignant intraductal papillary mucinous neoplasm: A rare case report and literature review. Issue 23 (June 2017) - Li, Bing-Qi; Liu, Qiao-Fei; Chang, Xiao-Yan; Hu, Ya; Chen, Jie; Guo, Jun-Chao
Abstract: Rationale: Carcinosarcoma, an extremely rare pancreatic primary tumor, is characterized by coexistence of both carcinomatous and sarcomatous components. Due to its rarity, the clinical manifestation and imaging features have not been recognized. An accurate diagnostic method has not been available and a widely accepted guidelines instructing treatment has not been established. Patient concerns: We present an uncommon case of pancreatic carcinosarcoma (PCS) which has been preoperatively diagnosed as pancreatic malignant intraductal papillary mucinous neoplasm. A radical resection, including total pancreatectomy (TP) and splenectomy, was performed. Diagnosis: The diagnosis of PCS was confirmed by postoperative pathology. Interventions: A radical resection, including TP and splenectomy, was performed. The patient was followed up by abdominal contrast-enhanced computed tomography scan and blood tumor marker examination. Outcomes: The patient is still alive and self-sufficient 7 months after the surgery. No evidence of tumor recurrence is found during follow-up. Lessons: Although, until recently, there are no widely accepted guidelines instructing treatment for PCS, a radical resection is still a possible way. All the pancreatic neoplastic patients with high surgical risk should be transferred to a specialized high-volume pancreatic center to get precise preoperative evaluation, fine operation technique, and careful postoperative management. Abstract : Supplemental Digital Content is available in the text